Speech perception in noise and sound localization using different microphone modes in pediatric bilateral cochlear implant users. (May 2022) - Müller, Verena; Krause, Jasmin; Klünter, Heinz Dieter; Streicher, Barbara; Lang-Roth, Ruth
Abstract: Objective: The aim of the study was to investigate if a directional microphone mode improves speech perception in noise and sound localization in experienced pediatric bilateral cochlear implant users. Methods: 15 bilaterally implanted children were included in the analysis. Speech perception in 4 noise conditions (S0 N0, S0 N90, S0 N-90, S0 N180 ) and sound localization were measured when using the OPUS 2 audio processor (omnidirectional mode) and the SONNET audio processor (omnidirectional and natural mode). Results: Speech perception in all 4 noise conditions was better with the SONNET natural mode than with the omnidirectional mode of either SONNET or OPUS 2. The root-mean-square error of the sound localization test was smaller with the natural mode of SONNET than with the omnidirectional mode of either SONNET or OPUS 2. The performance of the audio processors in the omnidirectional mode did not differ significantly except in the S0 N0 condition of the speech perception test. Conclusion: The natural microphone mode of the SONNET audio processor improved speech perception in noise and sound localization in bilaterally implanted children. Highlights: Bilaterally implanted children benefit from a natural microphone mode. SRTs and localization abilities improve with a natural microphone mode. SONNET processor use recommended with natural instead of omnidirectional mode.